Unlocking the Secrets of Successful Knowledge Transfer Among Software Project Managers: A Mixed-Methods Study - Nontouch Srisuksa; Mongkolchai Wiriyapinit; Pattarasinee Bhattarakosol; Thadathibesra Phuthong (Journal of Human, Earth, and Future)
Objectives: This study combined qualitative and quantitative sequential exploratory mixed-method approaches to identify the success factors of knowledge transfer effectiveness with software project managers and investigate how these factors impacted knowledge transfer effectiveness. Methods/Analysis: The qualitative research component included twelve senior and junior project managers, while the quantitative component involved a cross-sectional survey of 212 completed responses from software project managers. Findings: The results suggested that two influential factors as knowledge providers and knowledge transfer environment had a significant effect on knowledge transfer effectiveness. Novelty/Improvement: The research results enhance the operational capability of software project supervision and contribute to the improvement of knowledge transfer for software project managers operating in teams.